МОНГОЛЫН СОНГОГЧДЫН ИРЦ, ТҮҮНД НӨЛӨӨЛӨГЧ ХҮЧИН ЗҮЙЛС (ЗАЛУУЧУУДЫН ЖИШЭЭН ДЭЭР) - Н.Мягмарцоож (Politology, 2024)
In the words of L. Diamond, "Low participation of voters means weak immunity for democracy," underscoring the crucial role of elections in fostering democratic development. This paper explores the dynamics of voter turnout in Mongolia, focusing on the example of the youth demographic. The 2021 presidential election witnessed a marginal decrease of 0.7% in turnout among 18-35-year-olds compared to the 2016 election, and a more substantial drop of 11.1% from the 2020 turnout (ages 18-25). This decline can be attributed, in part, to the direct social impact of the pandemic, while various other factors, including political, social, economic, systemic, and individual influences, have played a role in shaping voter participation. Investigating the intricacies of the factors affecting voter turnout requires specialised efforts due to the time-consuming and meticulous nature of the process. Such endeavours involve a comprehensive examination of the country’s socio-political system and the prevailing social conditions. Notably, the turnout of young people aged 18-35, who make up 44% of Mongolia’s voting-age population, is disheartening. The fact that only half of this demographic engages in the electoral process signals a significant issue that demands attention and resolution. Addressing this challenge is imperative for strengthening the democratic fabric of Mongolia.